Determining Awareness of Vitamin D Necessity, Deficiency and its Appropriate Attainment among Medical undergraduate students of a private medical college: A Descriptive cross-sectional study - Ismail Mazhar, Mir Muhammad Rai, Qudsia Umaira Khan, Miranti Dewi Pramaningtyas, Kurrat Ul Aaien, Robass Zia, (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: To assess the awareness of the necessity, deficiency of vitamin D, and knowledge about its appropriate attainment among the medical students at Combined Military Hospital Lahore Medical College (CMH LMC) Methods: The study undertaken was an observational cross-sectional one conducted among the medical students of CMH LMC. A structured questionnaire was distributed among the medical students from first-year to fifth-year levels. The questionnaire consisted of two parts. The first part was based on socio-demographic information like age, sex, nationality, and the second half were based on questions regarding awareness of the benefits, deficiency and, attainment of Vitamin D. Results: The results were likely to highlight the mean awareness score with poor and good awareness identified among medical students. The questionnaire evaluated awareness regarding the main source and dietary source of vitamin D like milk, cheese, and fish; factors that affect vitamin D manufacture; the influence of vitamin D on health, and effects of its deficiency on body health; identifying high-risk groups; and significance of supplements in overcoming deficiency. Practical implication: The study would help increase and improve awareness of vitamin D necessity and deficiency issues among medical students. The awareness in the new generation of professionals can impact the evolution of future health education programs, policy development, the construction of social rules, and views about health and health-endorsing attitudes. Conclusion: The study concluded that the respondents were more aware of the necessity of vitamin D (M = -.05) and less aware of the deficiency and attainment level of vitamin D. (M = -.32; M = -.36) respectively. Keywords: Vitamin D, awareness, deficiency, attainment, medical students, health